Class participation in the Nanyang Business School - Gan, Eddie Eng Hui (2008)
Class participation has been increasingly used as a grading tool for various subjects taken in Nanyang Business School (NBS). It is widely viewed that the skills learnt in the classroom discussions will be highly valuable in the workplace. This study seeks to increase our knowledge of class participation trends in NBS.